Seismic Analysis of G+10 Structure Considering Flat Slab Using ETAB Software - Sudha Lakda; Sudha Lakda; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Civil Engineers are facing a great challenge in structural designing. The design must fulfil various parameters which include economical structure, durability and serviceability. But taking these points in mind it becomes very difficult for an Engineer to fulfil all these requirements at a time when a design is performed manually. This digital tool used in civil engineering and comparing their results by taking in mind the requirements of the above points. In this research process a building is taken for analysis and design on well-known Software ETABS. In this study we are comparing a G+10 High rise building frame considering three different slab conditions i.e. conventional slab, flat slab and flat slab with staggered beams. For analysis we are utilizing analysis tool etabs.